Flow and reactive transport in porous media induced by well injection: Similarity solution - Van Duijn, C. J. (Hans); Knabner, Peter (IMA Journal of Applied Mathematics, 1994)
The authors study concentration profiles of solutes undergoing equilibrium absorption in the vicinity of a water well. For the case of a contamination event, the limit problem of vanishing well radius, which is of self-similar nature, is analysed in detail. Existence, uniqueness, and qualitative properties of solutions of the corresponding ordinary differential equations are shown. Some numerical examples are also presented. © 1994 Oxford University Pres